A Systematic Study of Cataract Surgery in People with Diabetes Mellitus (International Journal of Food and Nutritional Sciences, 2022)
India is regarded as the diabetes capital of the world, and diabetic patients make up a sizable share of cataract surgery patients. In light of this, we evaluated the fundamentals and recommendations for treating cataract in people with diabetes. When treating patients with diabetic cataracts, the preoperative, intraoperative, and postoperative aspects are of the utmost significance. Prior to cataract surgery, early detection and treatment of diabetic retinopathy or maculopathy have a significant impact on the final visual prognosis and are crucial in the perioperative decision-making process. We may be able to better manage these individuals overall and improve the outcomes if we have a better grasp of the numerous elements that contribute to cataract surgery in diabetic patients having a favourable outcome.